Defective Suppressor of Cytokine Signaling 1 Signaling Contributes to the Pathogenesis of Systemic Lupus Erythematosus - Wang, Huixia; Wang, Jiaxing; Xia, Yumin (Frontiers in Immunology, 2017)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease involving injuries in multiple organ systems. Exaggerated inflammatory responses are characterized as end-organ damage in patients with SLE. Although the explicit pathogenesis of SLE remains unclear, increasing evidence suggests that dysregulation of cytokine signals contributes to the progression of SLE through the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway. Activated STAT proteins translocate to the cell nucleus and induce transcription of target genes, which regulate downstream cytokine production and inflammatory cell infiltration. The suppressor of cytokine signaling 1 (SOCS1) is considered as a classical inhibitor of cytokine signaling. Recent studies have demonstrated that SOCS1 expression is decreased in patients with SLE and in murine lupus models, and this negatively correlates with the magnitude of inflammation. Dysregulation of SOCS1 signals participates in various pathological processes of SLE such as hematologic abnormalities and autoantibody generation. Lupus nephritis is one of the most serious complications of SLE, and it correlates with suppressed SOCS1 signals in renal tissues. Moreover, SOCS1 insufficiency affects the function of several other organs, including skin, central nervous system, liver, and lungs. Therefore, SOCS1 aberrancy contributes to the development of both systemic and local inflammation in SLE patients. In this review, we discuss recent studies regarding the roles of SOCS1 in the pathogenesis of SLE and its therapeutic implications.